Study on corrosion mechanism and the risk of the shale gas gathering pipelines. (October 2021) - Liao, Kexi; Qin, Min; He, Guoxi; Yang, Na; Zhang, Shijian
Highlights: The multi factors synergistic corrosion mechanism is determined. The low-lying area and downhill section are identified as corrosion sensitive areas. According to the EFR curves, high risk corrosion defects are identified. Abstract: Corrosion and perforation accidents often occur in shale gas gathering and transportation pipelines, which causes serious economic losses. The medium in shale gas gathering pipelines is complex, and the corrosion rate is fast under the combined action of many factors. In this paper, the corrosion mechanism of shale gas gathering and transportation pipelines was studied by field data analysis and experiments. By means of multiphase flow simulation analysis and magnetic flux leakage internal detection, the characteristics and distribution of pipeline corrosion defects were identified, and the corrosion sensitive area was further determined. The results show that in the shale gas gathering pipelines, there were multiple corrosive media of CO2, O2 and SRB. The local corrosion was more serious under the promotion of Cl - and low liquid flow rate. The 3–9o'clock position on the low-lying and uphill section of the pipelines were the corrosion sensitive areas. Through the analysis of internal corrosion mechanism and ERF curves, there were many high-risk corrosion areas in the pipelines.